In-cycle control for stabilization of homogeneous charge compression ignition combustion using direct water injection. (15th April 2019) - Wick, Maximilian; Bedei, Julian; Gordon, David; Wouters, Christian; Lehrheuer, Bastian; Nuss, Eugen; Andert, Jakob; Koch, Charles Robert
Highlights: New architecture for modeling homogenous charge compression ignition. Heat release in intermediate compression as correlation for combustion phasing. Closed-loop in-cycle control using direct water injection. Combustion stabilization in terms of combustion phasing and load. Abstract: Homogeneous charge compression ignition offers a high potential for the reduction of CO 2 and NO x raw emissions; however, its use entails problems that are associated with low combustion stability, especially at the limits of the operating range. The recirculation of exhaust gases inside the combustion chamber by using a negative valve overlap leads to a strong coupling of consecutive cycles. The cyclic coupling induces phases of unstable operation after the occurrence of stochastic outlier cycles with misfire or incomplete combustion. These unstable phases are marked by reduced efficiency and increased emissions. Two in-cycle closed-loop control algorithms, which focus on the heat release in the intermediate compression, are presented in this article. To control the combustion process, direct water injection is used to ensure a direct influence on the temperature level in the combustion chamber; subsequently this influences combustion phasing. The decoupling of consecutive cycles serves to reduce deviations in the indicated mean effective pressure and crank angle position of 50% mass fraction burned. To develop a suitable controller, a first-order autoregressive model of homogeneous charge compression ignition combustion is split into intermediate compression and main combustion phases. Moreover, unstable sequences are analyzed in the time domain to identify appropriate in-cycle control concepts. The control concepts are developed based on the heat release in the intermediate compression as a strong correlation factor for consecutive cycles. To realize fast control interventions, a real-time cylinder pressure analysis as well as the control algorithms are implemented on a field-programmable gate array. The control algorithms are validated on a single-cylinder research engine and compared with conventional operation without in-cycle control. Results show a significant increase in the stability of combustion phasing and load by means of in-cycle control.